Analysis of affected surface zone created by different cutting technologies - Kučerová, Ludmila; Račický, Antonín; Tichá, Iveta (Manufacturing Technology Journal, 2020)
Three cutting technologies, plasma, laser, and acetylene, were used to produce the same geometry of a hole with 33 cm diameter. The plates of the same steel St-37 (1.0038, ČSN 11375) with a thickness of 50 mm were used in all three cases and the aim of the work was to evaluate and compare micro-structure changes of the cut surfaces. Longitudinal and transverse samples were taken from all cuts for subsequent analysis. Light and scanning electron microscopy of surface and below-surface areas were carried out at all samples. Hardness profiles were determined by micro-hardness and nano-hardness measurements. Based on these results, the depth of material that was influenced by cutting was established by image analysis of light micrographs, micro-hardness measurement and nano-hardness measurement. It was found out, that all three technologies influence significantly micro-structure and surface hardness of cut steel. Acetylene cutting resulted in the deepest affected zone consisting of several layers with gradually changing microstructures based on various ferritic-carbidic morphologies.
Keywords: Laser; Plasma; Acetylene; Surface modification